1995
DOI: 10.2190/ng68-hkel-07ht-a1e3
|View full text |Cite
|
Sign up to set email alerts
|

Personal Attributes and Computer Writing Quality

Abstract: This article reports the results of a study testing whether any of seventeen personal attributes related to the quality of documents university undergraduates wrote by hand and on the computer. Chi-square analysis showed significant differences for age, class, and word processing and keyboarding experience. The researchers concluded that some attributes do relate to computer writing quality and suggest further study to benefit computer writers and computer writing curriculum and instruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Munro 2002;Cox and Abbott 2004;Wentling et al 2006) and therefore affect the instruments that need to be used by researchers. Previous research has also shown that different types of ICT resources will have different effects on students' learning, for example, using science simulations to correct students' misconceptions and alternative frameworks (Cox 2000); using data handling software to improve students' abilities to apply binary logic (Cox and Nikolopoulou 1997); and using word-processing in English to reduce punctuation and grammatical mistakes (Barker and Pearce 1995). It is clear that from these and numerous other examples that the contribution of ICT to students' learning was very dependent upon the type of ICT resource and the subject in which is was being used.…”
Section: The Problem About the Different Effects Of Specific Types Ofmentioning
confidence: 99%
“…Munro 2002;Cox and Abbott 2004;Wentling et al 2006) and therefore affect the instruments that need to be used by researchers. Previous research has also shown that different types of ICT resources will have different effects on students' learning, for example, using science simulations to correct students' misconceptions and alternative frameworks (Cox 2000); using data handling software to improve students' abilities to apply binary logic (Cox and Nikolopoulou 1997); and using word-processing in English to reduce punctuation and grammatical mistakes (Barker and Pearce 1995). It is clear that from these and numerous other examples that the contribution of ICT to students' learning was very dependent upon the type of ICT resource and the subject in which is was being used.…”
Section: The Problem About the Different Effects Of Specific Types Ofmentioning
confidence: 99%
“…À ce chapitre, toutefois, il n'y a pas unanimité. Barker et Pearce (1995) arrivent à des conclusions différentes : selon eux, les élèves qui se sont peu familiarisés avec le traitement de texte commettent moins d'erreurs de ponctuation à l'écran (erreurs mécaniques), mais utilisent davantage de constructions passives (erreurs stylistiques). Les scripteurs mieux initiés à l'écriture technologique, au contraire, écriraient moins de phrases passives.…”
Section: Technologies Et Maîtrise Du Code Orthographiqueunclassified
“…I also describe the social interactions of my first-semester publications and language arts classes. While some research literature (Barker & Pearce, 1995;Bonk & King, 1998;Daiute, 1986;Knudson, 1995;Sudol, 1985) suggests that writing instruction using computers heightens students' interest and self-esteem, few studies examine whether technology improves middle-level students' actual writing.…”
Section: Chapter I Introductionmentioning
confidence: 99%